Dark Wolf [compact disc, unabridged] : a Carpathian novel - Feehan, Christine (Feehan, Christine. Carpathian novel., 2014)
Skyler Daratrazanoff always recognized the miracle that was Dimitri Tirunul, a man beyond any dream that had ever engaged her nights. But she was human. Vulnerable. He was Carpathian. Nearly immortal. She was nineteen. He was an ancient. Yet she held half his soul, the light to his darkness. Without her, he would not survive. Caught between the two warring species, Dimitri has spent centuries hunting the undead to keep his people free, and humans safe.